Dialysate interleukin-6 predicts increasing peritoneal solute transport rate in incident peritoneal dialysis patients - Cho, Yeoungjee (BioMed Central, 2014)
BACKGROUND: Repeated exposure to peritoneal dialysis (PD) solutions contributes to cumulative intraperitoneal inflammation and peritoneal injury. The present study aimed to explore the capacity of dialysate interleukin-6(IL-6) to a) predict peritoneal membrane function and peritonitis in incident PD patients, and b) to evaluate the influence of neutral pH, low glucose degradation product (GDP) PD solution on dialysate IL-6 levels. METHODS: The study included 88 incident participants from the balANZ trial who had completed 24-months of follow-up. Change in peritoneal solute transport rate (PSTR) and peritonitis were primary outcome measures, and the utility of IL-6 and IL-6 appearance rate (IL-6 AR) in predicting these outcomes was analyzed using multilevel linear regression and Cox proportional hazards models, respectively. Sensitivity analyses were performed by analyzing outcomes in a peritonitis-free cohort (n = 56). RESULTS: Dialysate IL-6 concentration significantly increased from baseline to 24 months (mean difference 19.07 pg/mL; P < 0.001) but was not affected by the type of PD solution received (P = 0.68). An increase in PSTR from baseline was associated with higher levels of IL-6 (P = 0.004), the use of standard solutions (P = 0.005) and longer PD duration (P < 0.001). Baseline IL-6 level was not associated with a shorter time to first peritonitis (adjusted hazard ratio 1.00, 95% CI 0.99-1.00, P = 0.74). Analysis of IL-6 AR as well as sensitivity analyses in a peritonitis-free cohort yielded comparable results. CONCLUSION: Dialysate IL-6 concentration increased with longer PD duration and was a significant, independent predictor of PSTR. The use of biocompatible PD solutions exerted no significant effect on dialysate IL-6 levels but did abrogate the increase in PSTR associated with standard PD solutions. This is the first study to examine the impact of biocompatible solutions on the utility of IL-6 in predicting PSTR and peritonitis.